1997
DOI: 10.1159/000121276
|View full text |Cite
|
Sign up to set email alerts
|

On the Surgical Treatment of Refractory Epilepsy in Tuberous Sclerosis Complex

Abstract: The role of surgery in the treatment of refractory epilepsy (RE) in tuberous sclerosis complex (TSC) is poorly defined. Four patients with RE and TSC were evaluated for epilepsy surgery from 1994 to 1996. Three of four patients developed infantile spasms within 5 months of birth. These progressed to frequent complex partial and generalized tonic/myoclonic seizures refractory to antiepileptic drug therapy. Neuroimaging revealed typical findings of TSC including calcified lesions consistent with hamartomas. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 12 publications
(17 reference statements)
1
36
1
Order By: Relevance
“…Of nine operated cases reported by Bebin et al, six became seizure-free and two had a significant seizure reduction [5]. Other authors also report good results of surgical treatment in TSC [3,4,6,13]. Seizure outcome was not classified by Engel criteria in any of the mentioned publications but the overall percentage of seizure-free patients after surgery is 50 ± 60 %.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of nine operated cases reported by Bebin et al, six became seizure-free and two had a significant seizure reduction [5]. Other authors also report good results of surgical treatment in TSC [3,4,6,13]. Seizure outcome was not classified by Engel criteria in any of the mentioned publications but the overall percentage of seizure-free patients after surgery is 50 ± 60 %.…”
Section: Discussionmentioning
confidence: 99%
“…Ictal seizure patterns (SzP) and subclinical SzP were found in only one location in three patients (no. 4,7,8), in one location and generalized in patients 5 and 6, unilateral in patients 2 and 9, in two locations and generalized in patient 3, and bilateral in patient 1. The patterns from invasive recording with subdural grid electrodes were strongly localized to one focus or tuber.…”
Section: Eeg Datamentioning
confidence: 92%
See 1 more Smart Citation
“…Up to one third of children affected with TSC develop infantile spasms; vigabatrin is the preferred treatment in these patients [44]. Several studies have shown excellent results once epileptogenic tubers were removed from individuals with TSC complicated by drug-resistant seizures [45,46]. …”
Section: Syndromic Causesmentioning
confidence: 99%
“…The assessment of whether one leading seizure source is responsible for all or most of the patient's seizures therefore is of critical importance during presurgical evaluation and usually requires invasive recordings. In recent studies, MEG was useful for better defining the leading epileptogenic focus in patients with tuberous sclerosis [104,105].…”
Section: Tuberous Sclerosismentioning
confidence: 99%